Translation of Malaysian legal terminology and lawyers' perspectives on linguistic borrowing / Phoebe Lim Ian Yee - Lim, Phoebe Ian Yee (2012)
This dissertation studies the translation of legal terminology from the English to the Malay language, in particular borrowings from English. The purpose of this study is to investigate the forms and functions nature of these legal borrowings and their usage among legal professionals. The legislative text of Evidence Act 1950 is used as the study data. Textual analysis is done based on Mashudi Kader’s (1994) categorisations of the source of Malay legal terms with some modification adapted from Newmark (1988) and Haugen (1953). Interviews and questionnaires were also used as instruments to find out lawyers’ reactions towards legal borrowings and their problems and solutions in using these borrowings. Results show that 33% of legal terms in Evidence Act consist of legal borrowings. Generally, lawyers are comfortable in using legal borrowings. They prefer the English term or its borrowing rather than a translated native term. Some problems acknowledged by the lawyers are their limited command of the Malay language, the lack of specific words in the Malay language, and the unintelligible nature of the legal borrowings to clients. To overcome these problems, lawyers engage in much explanation by using layman words or substitute the borrowings with simpler yet synonymous words. Lawyers’ preference in using legal borrowings suggests two things: the lawyers’ reluctance to attach new linguistic labels to legal concepts to which a label already exist in the English language and their readiness to assimilate English legal concepts into the Malay language for the purpose of accuracy and good justice at the expense of “language purity.”